2021
DOI: 10.1111/jfbc.14018
|View full text |Cite
|
Sign up to set email alerts
|

Potential metabolic activities of raspberry ketone

Abstract: Novel food and food compounds interventions have attracted a lot of attention nowadays for the prevention and treatment of metabolic diseases. Raspberry ketone (RK) is aromatic compound found within red fruits and berries, has been used as an over‐the‐counter product for weight loss. However, actually, the effect of RK on weight loss is still controversial, and the mechanism is largely unknown. Besides, in vivo and in vitro studies have demonstrated the beneficial effect of RK on the development of other metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 69 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…Rhododendrol (4-(4-hydroxyphenyl)-2-butanol; ROH) is present in Betula platyphylla and Acer nikoense Maximowicz ( 14 , 15 ). When administered orally to mammals, RK is metabolized via several pathways ( 16 ). ROH, formed by the reduction of the ketone group of RK, is excreted as a major metabolite after a single oral administration in rats, guinea pigs, and rabbits ( 17 ), suggesting that RK is reductively metabolized in the small intestine or liver (first-pass effect) ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Rhododendrol (4-(4-hydroxyphenyl)-2-butanol; ROH) is present in Betula platyphylla and Acer nikoense Maximowicz ( 14 , 15 ). When administered orally to mammals, RK is metabolized via several pathways ( 16 ). ROH, formed by the reduction of the ketone group of RK, is excreted as a major metabolite after a single oral administration in rats, guinea pigs, and rabbits ( 17 ), suggesting that RK is reductively metabolized in the small intestine or liver (first-pass effect) ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in cells and rodents have suggested an important role for Raspberry ketone (RK) in hepatic/cardio/gastric protection and as an anti-hyperlipidemic, anti-obesity via mediating activation of PPAR-α ( 84 ). RK has been used as an over-the-counter weight loss product, but it is still controversial, and the mechanism is still unknown.…”
Section: Pharmacological Effects Of R Chingii Humentioning
confidence: 99%
“…Raspberry ketone (RK), 4-(4-hydroxyphenyl)-butan-2-one, is a product of the phenylpropanoid pathway in various plants including raspberries (Rubus idaeus L.) where it serves as an attractant for pollinators and fruit flies . It was mainly used in the food and fragrance industry until it was popularized as having a positive effect on weight loss . Since then, it has been included in a range of nutraceuticals aimed at the weight loss market.…”
Section: Introductionmentioning
confidence: 99%
“… 1 It was mainly used in the food and fragrance industry until it was popularized as having a positive effect on weight loss. 2 Since then, it has been included in a range of nutraceuticals aimed at the weight loss market. Due to the low levels of RK present in plant sources, the majority of commercial RK is synthetic and can therefore only be marketed as a “nature identical” ingredient.…”
Section: Introductionmentioning
confidence: 99%